2001
DOI: 10.1159/000050014
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Tubular Uptake of <i>L</i>-3,4-Dihydroxyphenylalanine in Streptozotocin-Induced Diabetic Rats

Abstract: Background/Aims: This study determined alterations in renal dopamine production in streptozotocin-treated rats and explored the mechanisms underlying this alteration. Methods: Streptozotocin (65 mg/kg) or vehicle was administered to 3-month-old male Wistar rats. Treated animals had hyperglycemia, glycosuria and increased diuresis, natriuresis and excretion of L-dopa. Urinary dopamine and dihydroxyphenylacetic acid were similar to those in control animals. The production of dopamine by renal cortex slices from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…Selective depletion of intrarenal dopamine production accelerated diabetic nephropathy in our studies, consistent with alterations in intrarenal dopamine production that has been previously reported in both experimental and human diabetic nephropathy (15,36,4042). These studies further confirm that intrarenal dopamine plays an important modulatory role in development and progression of renal injury in diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Selective depletion of intrarenal dopamine production accelerated diabetic nephropathy in our studies, consistent with alterations in intrarenal dopamine production that has been previously reported in both experimental and human diabetic nephropathy (15,36,4042). These studies further confirm that intrarenal dopamine plays an important modulatory role in development and progression of renal injury in diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that abnormalities in the intrarenal dopaminergic system may be an underlying contributing factor to increased renal salt and water reabsorption in diabetes (15,16). Diabetes is characterized by elevated glomerular filtration rate (GFR) and sodium retention due to increased proximal reabsorption and reduced luminal NaCl delivery to the macula densa (17,18).…”
mentioning
confidence: 99%
“…Indeed, previous results from our laboratory have described an increased renal excretion of L-dopa in streptozotocin-induced diabetic rats [5].…”
Section: Introductionmentioning
confidence: 79%
“…Early studies demonstrated that the uptake of L-dopa into the proximal tubules is an active process, with high structural specificity [7]. In previous studies from our laboratory the transport of L-dopa into proximal tubules has been shown to be impaired in aged rats [2], inhibited by β 2 -adrenergic receptor signalling [6] and by high glucose [5]. The reabsorbed L-dopa is converted into dopamine by the cytoplasmic aromatic Lamino acid decarboxylase [23], the intracellular availability of L-dopa being the limiting step in renal dopamine synthesis [2,23].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a complex of metabolic disease characterized by hyperglycemia, diminished insulin production, impaired insulin action, or a combination of both resulting in the inability of glucose to be transported from the blood stream into the tissues, which in turn results in high blood glucose levels and excretion of glucose in the urine [1]. Cell functions involved in the action of insulin receptor binding enzyme and transporter activities are controlled by membrane properties [2].…”
Section: Introductionmentioning
confidence: 99%